1997
DOI: 10.1093/oxfordjournals.aje.a009262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Sources of Traumatic Spinal Cord Injury Surveillance Data in Colorado

Abstract: The purpose of this study is to evaluate the sources reporting hospitalized spinal cord injury cases to the statewide, population-based surveillance system in Colorado for the year 1994. Three reporting sources were evaluated: clinical contact persons, medical records departments, and a centralized statewide hospital discharge database. Two evaluation strategies were utilized; these include both measures of accuracy and estimates of missed cases. For the latter, capture-recapture techniques were used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Nonetheless, a population-based study in Colorado confirmed 87% and 90% sensitivity for TSCI codes. 43 Third, data did not include information on behavioral, clinical, and psychosocial risk factors that could determine the risk associated with the comorbid conditions of interest. Fourth, it is possible that there may be residual confounders, which we have not accounted for in our study.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Nonetheless, a population-based study in Colorado confirmed 87% and 90% sensitivity for TSCI codes. 43 Third, data did not include information on behavioral, clinical, and psychosocial risk factors that could determine the risk associated with the comorbid conditions of interest. Fourth, it is possible that there may be residual confounders, which we have not accounted for in our study.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…closed head injury not further specified) rather than a distinct injury code. Future research should investigate the discrepancies between the two databases to determine whether the mild TBI cases were missed or are false positives as well as why there are large discrepancies by age and gender [12]. Among the TBI cases identified by the MHD data set, there was good concordance between the MHD and the medical records data regarding the presence of anatomic injuries, specifically skull fractures and intra-cranial lesions.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, capture-recapture studies are employed in assessments of the completeness of cancer [18] and SCI registries [19]. This study was designed to assess the prevalence of SCI in Iran, using a 3-source capture-recapture method [20,21]. …”
Section: Introductionmentioning
confidence: 99%